Understanding the Nusantara Thought and Local Wisdom as an Aspect of the Indonesian Education - Meliono, Irmayanti (TAWARIKH, 2011)
ABSTRACT: This paper discusses of the Nusantara thought, local wisdom, and the Indonesian education. The complex, dynamic, and eclectic nature of the Indonesian cultures are based on the ethnics that have settled in Indonesia for some centuries and the foreign cultures of India, Arab, Dutch, China and others. The synthesis of these mixed cultures has caused the people of Nusantara then, now Indonesia, have a certain perception on a reality of life. It reflects the awareness of the people of Nusantara of their world-view and thoughts about values, symbols, and local wisdom. Therefore, the Nusantara thought, local wisdom, and multiculturalism are appropriate teaching material for the education of the Indonesian youth as they edify some values such as nationalism, harmony, and moral to build an identity. Finally, it is to institute an educational program in all levels such as teaching a cultural overview and a correct teaching method to present a teaching material using the Nusantara thought, local wisdom, and multiculturalism. This is a critical step to take as globalization has been fast in the field of education, science, and technology. KEY WORDS: Culture of Indonesia, the Nusantara thought, local wisdom, multiculturalism, and education of the young generation.Â About the Author: Dr. Irmayanti Meliono is a Lecturer at the Departement of Area Studies, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok 16424,Â West Java, Indonesia. She can be reached at: irmayanti_m@yahoo.comHow to cite this article? Meliono, Irmayanti. (2011). âUnderstanding the Nusantara Thought and Local Wisdom as an Aspect of the Indonesian Educationâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.221-234. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 2, 2011); Revised (March 5, 2011); and Published (April 28, 2011).